SPEECH ACT STRATEGY UTTERED BY EMMA WATSON AND MALALA YOUSAFZAI AS THE INSTRUMENT OF EMPOWERMENT - Ika Setyowati Sutedjo (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2021)
Women’s voice has been heard by the society for the past few years. There are a lot of movements created by women to support each other, for example Women’s March, Time’s Up, #MeToo and HeForShe. This movement will lead to more recognition of women in various expertise. Consequently, those amazing women are able to meet in one situation. Certain situation leads women to do a conversation. The conversation between women also includes different kinds of speech act. This study aims to find the speech act uttered by Emma Watson and Malala Yousafzai as the instrument of empowerment. The result of the study shows that Emma Watson and Malala Yousafzai are mostly use directive speech act in their speeches. The purpose of directive speech act is to make people to do something. Emma and Malala use directive speech act to empower people to accomplish something. The use of directive speech act also related to the third wave feminism movement. This movement establishes women to be bold, empowered, and brave. So, third wave of feminism also influences Emma and Malala as bold and empowered women. They empower other people to do something through their speech act because they are empowered women.